2019
DOI: 10.1039/c9gc03410b
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-free construction of trinuclear N-fused hybrid scaffolds by double nucleophilic aromatic substitution under microwave irradiation

Abstract: A green construction of trinuclear N-fused hybrid scaffolds by transition metal-free double C(sp2)–N coupling of 2-(2-bromoaryl)- and 2-(2-bromovinyl)benzimidazoles with 2-aminoazoles under microwave irradiation has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, as is the case for our recent report on the reaction of 2-(2-bromoaryl)-and 2-(2-bromovinyl)benzimidazoles with 2-aminoazoles, 3a was not produced at all in the absence of base and no other spots were observed except for both substrates on TLC (Table 1, entry 15). 8 Similar treatment of 1a with 2a under usual heating conditions screw-capped vial, 150 C for 20 h resulted in only 33% yield of 3a along with several unidentiable side products with complete conversion of 1a (Table 1, entry 16).…”
Section: Resultsmentioning
confidence: 96%
“…However, as is the case for our recent report on the reaction of 2-(2-bromoaryl)-and 2-(2-bromovinyl)benzimidazoles with 2-aminoazoles, 3a was not produced at all in the absence of base and no other spots were observed except for both substrates on TLC (Table 1, entry 15). 8 Similar treatment of 1a with 2a under usual heating conditions screw-capped vial, 150 C for 20 h resulted in only 33% yield of 3a along with several unidentiable side products with complete conversion of 1a (Table 1, entry 16).…”
Section: Resultsmentioning
confidence: 96%
“…Here again, from the reaction of 1 k with 2‐methoxybenzimidazoles ( 2 b , 2 c and 2 f ), the corresponding trinuclear N‐fused hybrid scaffolds 3 r – t were also formed in 60–68 % yields. To the best of our knowledge, limited examples are found for the synthetic method of such a trinuclear N‐fused hybrid scaffold like 3 k – t [11,12] …”
Section: Resultsmentioning
confidence: 99%
“…During the course of our recent efforts directed toward copper‐catalyzed and transition metal‐free synthesis of polynuclear N‐fused hybrid scaffolds via a C(sp 2 )−N coupling, we also recently reported that 2‐(2‐bromophenyl)benzimidazoles were coupled and cyclized with cyclic ureas as building blocks in the presence of CuI to produce scaffold A (Scheme 1, route d) [10,11] . In contrast to these precedents, the first transition metal‐free construction of scaffold A was achieved by a base‐mediated nucleophilic aromatic substitution (S N Ar) between 2‐(2‐bromophenyl)benzimidazoles and 2‐aminobenzimidazoles as building blocks (Scheme 1, route e) [12,13] . The present work started during the course of the development of a building block for the construction of scaffold A by such a transition metal‐free C(sp 2 )−N bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…[1] During the course of our continuous efforts directed toward developing new synthetic methods for polynuclear N-fused hybrid scaffolds under transition metal-catalyzed and transition metal-free conditions, [2] we reported on the synthesis of trinuclear N-fused hybrid scaffold A by basepromoted double C(sp 2 )-N coupling between 2-(2-bromoaryl)benzimidazoles and 2-aminobenzimidazole under transition metal-free condition (Scheme 1, route a). [3,4] The present work started during the course of application of such a protocol to the reaction with indole analogues to form trinuclear N-fused hybrid scaffolds, benzo [4,5]imidazo [1,2-c]indolo [1,2-a]quinazolines B (Scheme 1, route d). In contrast to widely known synthetic methods and biological activities of each homonuclear scaffold (indole, quinazoline, and benzimidazole) of scaffold B and binuclear scaffolds by the combination of such a homonuclear scaffold, only one report is found for the synthetic method of their trinuclear N-fused hybrid scaffold B.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that aryl halides are readily hydrodehalogenated in the presence of a copper catalyst. [7] The yield of 3a increased with elevating temperature up to 150°C ( Table 1, entries [1][2][3]. No significant change of the yield of 3a was observed with prolonging the reaction time and higher molar ratio of [2a]/[1a] (Table 1, entries 4 and 5).…”
Section: Introductionmentioning
confidence: 99%